THUNDERSTORM PREDICTION THROUGH STABILITY INDICES FOR LAHORE, PESHAWAR AND KARACHI, PAKISTAN - Sadiq, N. (The Nucleus, 2013)
An attempt is made here to develop a methodology to comprehend the forecast of thunderstorms through two important stability indices viz. George K Index and Total Totals Index for Lahore Peshawar and Karachi stations. The study is based on the analysis of 374 events during ten years (1996-2005). The findings infer mean values of K-Index as 35 and 25 for summer and winter, respectively, while threshold value of TT-Index comes out as 40 for the both seasons. The case study of July 30, 2006 is also incorporated for Karachi. The hypothesis and the most fitting ranges of different stability indices suggested in this research have yet to be testified and confirmed before the same can be used as one of the forecasting tools. This study will probably help the operational to make use of various stability indices and is expected to improve the weather forecast as this will be in addition to the convectional forecasting techniques now being used in Pakistan.